Pertussis in infants under one year old: Risk markers and vaccination status—A case-control study. Issue 17 (21st April 2015) - Zamir, Chen Stein; Dahan, Dana Bardugo; Shoob, Hanna
Highlights Low birthweight and high birth order were found to be independent risk markers for pertussis in young infants. A third of reported pertussis cases in infants occurred under age 2 months (currently recommended for the 1st pertussis vaccine dose). Reported pertussis cases over age 2 months were more likely to be unvaccinated and to have delayed vaccinations. In 2-4-month-old infants, 1 dose of pertussis vaccine gave significant protection against pertussis overall and pertussis hospitalization. The pertussis vaccine effectiveness increased with the number of vaccine doses.